(3TQM GdCQHYjf GdMOjK GdfhhjIs - (3GHf Objb GdYjOs; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s
(3ChdgG (B:s
(3GdMOjK GdChd Yf YeQ Hf GdNWGH CHj MaU CejQ GdeDefjf QVi Gddg Yfg bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B: ( (3EfeG GdCYeGd HGdfjGJ hEfeG dcd CeQA eG fhi s
(3BNQgG (B:s
(3hbO bGd Udi Gddg Ydjg hSde (B( (3eG CUQ ef ESJZaQ hEf YGO ai Gdjhe SHYjf eQI (B) (3hbGd CHh gQjQI QVi Gddg Yfg bGd QShd Gddg Udi Gddg Ydjg hSde (B((3MSf GdXf HGddg ef MSf YHGOI Gddg (B) (3hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs